Peningkatan Kemampuan Berpikir Kritis Peserta Didik melalui Penggunaan Media Video Animasi pada Materi Sistem Pernapasan Manusia di Kelas V SDN Rawamangun - Lintang Nursyifa Hidayat; Susi Winarni; Engga Dallion EW (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Critical thinking skills are essential competencies in 21st-century learning; however, many elementary school students still experience difficulties in analyzing information, evaluating evidence, drawing conclusions, and explaining their reasoning during science learning. This study aimed to describe the implementation of animated video media and improve students’ critical thinking skills in learning the human respiratory system in Grade V-C of SDN Rawamangun 02. The study employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, conducted from April to May 2026 in three cycles involving 30 students. Data were collected through observation, written tests, interviews, and documentation and were analyzed using descriptive quantitative and qualitative techniques. The results showed that the implementation of animated video media was carried out effectively, as indicated by the improvement in teacher performance from 75.00% in Cycle I to 95.00% in Cycle III. Students’ critical thinking skills also improved, as reflected in the observation results, which increased from 57.14% to 89.29%, and in the written test results, which increased from 50.00% to 86.67%. The improvement was evident in the aspects of analysis, evaluation, inference, and explanation. The findings indicate that animated video media can effectively enhance students’ critical thinking skills in science learning, particularly on the topic of the human respiratory system. Therefore, animated video media can serve as an alternative instructional medium to support the development of critical thinking skills in elementary schools.